Does Haste Make Waste? How Long Does It Take to Do a Good Regulatory Impact Analysis?. (April 2016) - Shapiro, Stuart; Morrall, John
We examine the relationship between the amount of information in a Regulatory Impact Analysis (RIA) and the time it takes to write and review the RIA. We find that the longer an agency spends developing the regulation and the longer that the Office of Information and Regulatory Affairs (OIRA) spends reviewing it, the more information in the analysis. However, the direction of causality is unclear. Better analyses may take more time to review. Or more review may make analyses better. We recommend increasing OIRA staff, which has advantages regardless of the direction of causality.